Un lugar para el arte. Rubén Darío y Eduardo Schiaffino (Documentos y cartas inéditas) - García Morales, Alfonso (Anales de Literatura Hispanoamericana, 2004)
This article is an attempt to reconstruct the relationship between Rubén Darío y Eduardo Schiaffino, the painter, critic and art historian who founded and directed Argentina’s National Museum of Fine Arts between 1896 and 1910. Darío and Schiaffino were at the head of a group of writers and painters who tried to lay claim to a social and physical place for art in the midst of the modernisation which was being lived by Buenos Aires at the end of the century. The unpublished documents and data which are here presented will lead to a more precise understanding of important aspects of Darío’s relation with Argentine culture: his network of friendships and protectors, his contacts with exhibitions and art collections, his participation in institutions, publications and polemics, his launching, parallel to the foundation of the Museum of Fine Arts, of Los raros and Prosas profanas, and the context of various of his texts, such as the artistic chronicles «Puvis de Chavannes» and «Rodin».